PENGARUH KUALITAS PELAYANAN DAN HEDONIC SHOPPING MOTIVATION TERHADAP TERCIPTANYA WORD OF MOUTH POSITIF MELALUI KEPUASAN KONSUMEN WISATA KULINER FOOD JUNCTION SURABAYA - Rini Novianti; Eva Desembrianita (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
This research aims to examine the effect of service quality and hedonic shopping motivation on positive word of mouth through customer satisfaction. The population of this research is customer of Food Junction in Surabaya. The number of sample about 98 respondents are taken with accidental sampling technique. Data are collected with questionnaires. To gain the result as the research goal, structural equation modelling were analyzed by partial least square (PLS) using Smart PLS 3.0. The results show that service quality and hedonic shopping motivation influence significantly on positive word of mouth through customer satisfaction. The results of this research have important implication to the manager of culinary center in order to improve excellent services by utilizing the hedonic customer that make customer satisfied, and finally creating a positive word of mouth as a beneficial promotion for the culinary manager.